Detection and treatment of Candida auris in an outbreak situation: risk factors for developing colonization and candidemia by this new species in critically ill patients. Issue 4 (3rd April 2019) - Ruiz-Gaitán, Alba; Martínez, Héctor; Moret, Ana María; Calabuig, Eva; Tasias, María; Alastruey-Izquierdo, Ana; Zaragoza, Óscar; Mollar, Joan; Frasquet, Juan; Salavert-Lletí, Miguel; Ramírez, Paula; López-Hontangas, José Luis; et al.
ABSTRACT: Background : Candida auris is an emerging, multidrug-resistant yeast causing hospital outbreaks. This study describes the first 24 months of the ongoing C. auris outbreak in our hospital and analyzes predisposing factors to C. auris candidemia/colonization. Research design and methods : A 12-month prospective, case-controlled study was performed including a total of 228 patients (114 colonized/candidemia and 114 controls). Data from the first 79 candidemia episodes and 738 environmental samples were also analyzed. Definitive C. auris identification was performed by ITS sequencing. Antifungal susceptibility was carried out by EUCAST methodology. Results : Polytrauma (32%), cardiovascular disease (25%), and cancer (17%) were the most common underlying condition in colonized/candidemia patients. Indwelling CVC (odds ratio OR, 13.48), parenteral nutrition (OR, 3.49), and mechanical ventilation (OR, 2.43) remained significant predictors of C. auris colonization/candidemia. C. auris was most often isolated on sphygmomanometer cuffs (25%) patient tables (10.2%), keyboards (10.2%), and infusion pumps (8.2%). All isolates were fully resistant to fluconazole (MICs >64 mg/L) and had significantly reduced susceptibility to voriconazole (GM, 1.8 mg/L). Conclusions : Predictor conditions to C. auris colonization/candidemia are similar to other Candida species. C. auris colonizes multiple patient's environment surfaces. All isolates are resistant to fluconazole and had significant reduced susceptibility to voriconazole.